2014
DOI: 10.1002/app.41177
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide‐montmorillonite nanocomposites as a drug delivery system: Preparation, release of 1,3,4‐oxa(thia)diazoles, and antimicrobial activity

Abstract: New microbicidal polyamides were prepared by the reaction of 5-phenyl-1,3,4,-oxadiazole-2-thiol, 5-phenyl-1,3,4-oxadiazole-2-amine, and 5-(4-chlorophenyl)21,3,4-thiadiazole-2-thiol with ethyl chloroformate followed by polycondensation with polyoxypropylenetriamine (Jeffamine T 403 ). The polyamides were modified to yield amine hydrochloride. The intercalation of polyamides into montmorillonite (MMT) was achieved through an ion exchange process between sodium cations in MMT and amine hydrochloride in the polyam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Although in vitro studies showed no antimicrobial effect, in vivo studies suggest that nanocomposites offer good antimicrobial activity. 72 New nano hybrid materials based on a combination of montmorillonite and pH sensitive positive charges polymer for encapsulating drugs to produce inorganic-organic nanocomposite are able to act as effective drug delivery systems (DDS). In this approach, the ionic liquid monomers are intercalated into montmorillonite and subsequently copolymerized with methacrylic acid.…”
Section: Polymer Based Nanocompositesmentioning
confidence: 99%
“…Although in vitro studies showed no antimicrobial effect, in vivo studies suggest that nanocomposites offer good antimicrobial activity. 72 New nano hybrid materials based on a combination of montmorillonite and pH sensitive positive charges polymer for encapsulating drugs to produce inorganic-organic nanocomposite are able to act as effective drug delivery systems (DDS). In this approach, the ionic liquid monomers are intercalated into montmorillonite and subsequently copolymerized with methacrylic acid.…”
Section: Polymer Based Nanocompositesmentioning
confidence: 99%
“…Moreover, similar to alginate film, incorporating montmorillonite increased tensile strength and decreased degradation and drug release rates of a polyester polyol acrylate-based film (Thatiparti et al 2010). Polyamide and polyacrylamide have also been studied as montmorillonite-mixed formulations (Kevadiya et al 2013;Salahuddin et al 2014).…”
Section: Poly(acrylic Acid) Formulationsmentioning
confidence: 99%
“…Sustained release was observed from the nanocomposites. In vivo studies showed that nanocomposites offer good antimicrobial activity . In this study, different ratios of 5‐phenyl‐1,3,4‐oxadiazole‐2‐thiol was loaded into 2,3‐dihydroxysuccinate, then reacted with Jeffamine (T 403 ).…”
Section: Introductionmentioning
confidence: 99%